Platform business transformation: A temporal perspective on strategy implementation - MACK, Daniel Z. (Institutional Knowledge at Singapore Management University, 2018)
The winner-takes-all nature of platform market competition is such that the success of a platform-based organization often depends on how rapidly it could scale-up from a startup to a dominant platform. However, we have very little processual knowledge about how and whether platform-based organizations become successful over time. Based on a two-year inductive field study of a platform-based organization, we show that top managers engage in temporal strategy making and paradox management to enable rapid platform scaling by enacting internal employee and external stakeholder resonance. Yet, rapid scaling destabilizes this resonance by escalating employee task expectations and exposing platform-related structural inefficiencies. Our findings suggest how rapid and agile strategic implementation of a platform strategy risks leading to a less agile and flexible organization over time.